The effect of multicultural attitude, learning style, and parents' job on the learning achievement of the students - Irawati, Ratrining Raras; Zamroni, Zamroni (Program Pascasarjana Universitas Negeri Yogyakarta, 2020)
The purpose of this research is to reveal the effect of multicultural attitude, learning style, and parents' job on the learning achievement of the students of senior high school in Magelang City, either partial or simultaneous. The research population was 771 grade XI students of social science of senior high schools in Magelang City, Indonesia, with a sample of 277 students. A multicultural attitude, learning style, and parents' job data were collected using questionnaires. In contrast, the economics learning achievement data were collected through an achievement test. The data were analyzed using multiple regression techniques. The study concludes that a multicultural attitude and parents' job positively affect economics learning achievement. But the learning style does not affect economic learning achievement. The multicultural attitude, learning style, and parents' job simultaneously affect the students of senior high school's economics learning achievement in Magelang City with a contributed of 5.1%.